ANALISIS PENGARUH MEKANISME TATA KELOLA PERUSAHAAN DAN MANAJEMEN LABA TERHADAP LIKUIDITAS PASAR SAHAM - Carolina, Agnes; Darsono, Darsono (Diponegoro Journal of Accounting, 2014)
The aim of this study is to examine the influence of corporate governance mechanisms and earnings management on trading volume. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange from 2009 to 2011. Sampling is done by using purposive sampling method. Sample of this study is composed of 177 companies during the 3-years observation. Hypotesis are tested by the use of multiple regression analysis. The results showed that board independence and earnings management has no significant effect on trading volume, while public ownership has significant effect on trading volume. Higher public ownership tends to higher the trading volume.